Cone‐beam computed tomography versus computed tomography‐guided ultrathin bronchoscopic diagnosis for peripheral pulmonary lesions: A propensity score‐matched analysis. Issue 5 (21st February 2021) - Kawakita, Naoya; Takizawa, Hiromitsu; Toba, Hiroaki; Sakamoto, Shinichi; Miyamoto, Naoki; Matsumoto, Daisuke; Takashima, Mika; Tsuboi, Mitsuhiro; Yoshida, Mitsuteru; Kawakami, Yukikiyo; Kondo, Kazuya; Tangoku, Akira
Abstract : Diagnostic yields of CT‐guided and CBCT‐guided transbronchial biopsy for peripheral pulmonary nodules were compared by propensity score‐matched analysis. Overall diagnostic yields were 47.9% for CT‐guided biopsy and 72.9% for CBCT‐guided biopsy. CBCT‐guided biopsy improved the diagnostic yield. ABSTRACT: Background and objective: CBCT‐guided TBB using a UTB under VBN is a useful method for the diagnosis of peripheral small pulmonary lesions. CBCT‐guided TBB using UTB under VBN has been used as an alternative to CT‐guided TBB. However, the advantage of CBCT‐guided TBB using UTB under VBN over CT‐guided TBB is still unknown. This study aimed to compare the diagnostic yield of CT‐guided TBB and CBCT‐guided TBB using a propensity score‐matched analysis. Methods: Patients with peripheral pulmonary lesions ≤30 mm were included. Lesions whose bronchus could not be determined by CT were excluded. A UTB and biopsy forceps were advanced to the target bronchus under VBN, 2D‐fluoroscopy and CT or CBCT. The CT‐guided and CBCT‐guided groups were matched for their propensity scores based on patient characteristics. Results: We retrospectively reviewed 93 patients in the CT‐guided group and 79 patients in the CBCT‐guided group for this study. Furthermore, 48 distinct examination pairs were generated by propensity score matching. In the overall diagnostic yield, the CBCT‐guided group showed better results (72.9%) than did the CT‐guided group (47.9%) ( P = 0.012). The median examination time lasted for 43 (IQR: 37–51) min in the CBCT‐guided group and 50 (IQR: 43–62) min in the CT‐guided group. The examination time in the CBCT‐guided group was significantly shorter than that of the CT‐guided group ( P = 0.001). Conclusion: CBCT‐guided TBB had a better diagnostic yield and shorter examination time than did CT‐guided TBB.